Monetary policy spillovers and the role of prudential policies in the European Union - Andra Coman (European Central Bank (ECB), 2023)
This paper empirically examines the extent to which prudential policies can help to reduce the macro-financial spillover effects of foreign monetary policy for all 28 EU countries. Using local projection methods, I show that EU countries with tighter prudential policies face significantly smaller, and less negative spillovers to bank credit and house prices from US, UK and EA monetary policy tightening shocks. Measures of a macroprudential policy nature such as capital buffers, lending standards restrictions and limits to credit growth appear to be particularly effective at mitigating the spillover effects of US monetary policy, while measures of a microprudential nature as minimum capital requirements, risk weights and limits on large exposures prove effective in mitigating spillovers effects of UK monetary policy. Results indicate that domestic prudential policies can dampen EU countries' exposure to foreign monetary policy and may be a useful tool in the face of spillovers coming from centre countries and within the EU.
Keywords: E52; E58; E61; F42; F45; 330; International spillovers; Local projections; Policy Interactions; Monetary policy; Prudential policy